Correlation between CD4 cell counts with mucocutaneous manifestations: study of HIV patients in Dr. Sardjito General Hospital, Yogyakarta - Satiti Retno Pudjiati; Nadia Akita Dewi; Sekar Sari Arum Palupi (Journal of the Medical Sciences (Berkala Ilmu Kedokteran), 2018)
Mucocutaneous disorders often seen in HIV patients with varying morbidity. The HIVprogression is characterized by the declining of CD4 cell counts and emergence ofmucocutaneous manifestations. The aim of the study was to evaluate the relationshipbetween CD4 cell counts with mucocutaneous manifestations in HIV patients. This wasa cross-sectional study based on medical records at Dr. Sardjito General Hospital duringthe period January 2011-December 2015. Data of patient’s age, sex, risk factors oftransmission, most mucocutaneous manifestations and CD4 cell count were gathered. Thecorrelation between CD4 cell counts with muscocutaneous manifestations were analyzedusing chi-square test. A total 928 patients were involved in the study. More than half ofthe patients were male (65.4%) and mostly, the patients aged 20-29 years (38.69%).The main risk factors for HIV transmission were unsafe sex (75%). The highest CD4 cellcounts was 1094 cells/mm3 and the lowest was 1 cell/mm3. We found 306 cases ofmucocutaneous manifestations. The most mucocutaneous manifestations was a fungalinfection (40.4%) with the highest infection type was oral candidiasis(33.8%); then noninfection(28%) with the highest type was drug eruption(35.9%); and tumors(0.5%) thatwas only Kaposi sarcoma cases. We also found sexually transmitted infections (STIs)(18.85%) with the highest cases was condyloma acuminata (49.3%). Statistical analysisshowed a significantly relationship between CD4 cell counts with a fungal infection(p <0.0001; OR= 3.8; 95% CI: 2.29 - 6.30), viral infection (p =0.0031; OR= 0.4;95% CI: 0.24-0.74) and parasitic infection (p=0.043; OR= 0.2; 95% CI: 0.06-0.61).In conclusion, alteration in CD4 cell counts affects opportunistic infections occurencein HIV patients. Lower CD4 cell counts (<200 cells/mm3) increases the risk of fungalinfection as much as 3.8 times. Higher CD4 cell counts (>200 cells/mm3) increases therisk of viral infection by about 2.5 times and parasitic infections as much as 5 times.